2021
DOI: 10.36953/ecj.2021.22349
|View full text |Cite
|
Sign up to set email alerts
|

Tree species diversity in Kalidhar forest of western Shiwaliks, Jammu, JK (UT)

Abstract: The present study was conducted in Kalidhar forest of western Shiwaliks, Jammu, JK (UT), to assess the tree diversity and undertake phytosociological analysis in three major land use (LU) classes i.e. Forest, Agriculture and Scrub area.  A total of 70, 50 and 50 sample plots of 0.1 ha were laid respectively in forests, scrub and agriculture LU classes. The study revealed that in forests possess a total 39 tree species belonging to 19 families and 31 genera, whereas, in scrub and agriculture lands a total of 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…But it is quite lower in comparison to the 197 plants from 87 families and 174 genera from Kathua district (Rao et al, 2015); 162 tree species from primary forests of Garo Hills, India (Kumar et al, 2006). Similar studies were done in J & K, where 35 plants species were recorded from shiwalik mountains of Azad J&K (Khanum et al, 2022); 39 trees species from kalidhar forest range of western shiwaliks (Sharma and Kumar, 2021); (Jan et al, 2021) reported 60 plant species belonging to 35 families in the temperate forest; 213 vascular plant species from mixed subtropical and temperate forests of Devi Pindiyan valley in trikuta hills of Northwest Himalaya (Thakur et al, 2019); 323 plant species from lower shiwalik hills (Sharma et al, 2015); 190 species from hills of north western Himalayas (Dutt et al, 2015). Although Protected Areas (PAs) play a key role for the harbouring elusive flora and fauna similarly our study area encompasses 3 wildlife sanctuaries (Nandni WLS, Surinsar-Mansar WLS-some part in samba and Ramnagar WLS) but we excluded the sanctuaries because our motive was to document trees species near to the villages and settlements in peri urban areas.…”
Section: Discussionsupporting
confidence: 59%
“…But it is quite lower in comparison to the 197 plants from 87 families and 174 genera from Kathua district (Rao et al, 2015); 162 tree species from primary forests of Garo Hills, India (Kumar et al, 2006). Similar studies were done in J & K, where 35 plants species were recorded from shiwalik mountains of Azad J&K (Khanum et al, 2022); 39 trees species from kalidhar forest range of western shiwaliks (Sharma and Kumar, 2021); (Jan et al, 2021) reported 60 plant species belonging to 35 families in the temperate forest; 213 vascular plant species from mixed subtropical and temperate forests of Devi Pindiyan valley in trikuta hills of Northwest Himalaya (Thakur et al, 2019); 323 plant species from lower shiwalik hills (Sharma et al, 2015); 190 species from hills of north western Himalayas (Dutt et al, 2015). Although Protected Areas (PAs) play a key role for the harbouring elusive flora and fauna similarly our study area encompasses 3 wildlife sanctuaries (Nandni WLS, Surinsar-Mansar WLS-some part in samba and Ramnagar WLS) but we excluded the sanctuaries because our motive was to document trees species near to the villages and settlements in peri urban areas.…”
Section: Discussionsupporting
confidence: 59%